PENGARUH KERAGAMAN PRODUK, HARGA DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN PADA SWALAYAN KPRI SINAR HARAPAN DI SITUBONDO - Muhammad Nur Fidyan Tesar Susanto; Edy Kusnadi Hamdun; Dwi Perwitasari Wiryaningtyas (Jurnal Mahasiswa Entrepreneurship (JME), 2026)
The purpose of the study was to determine the partial, simultaneous, and dominant influence of product quality, price, and location variables on consumers' buying interest. The data analysis method used in this study uses multiple linear regression analysis, t test to determine the influence partially, F test to determine the influence simultaneously, dominant test and coefficient of determination. Statistical tests of variable regression results (X1), (X2) and (X3) have a positive influence on the variable Purchase decision (Y), it is shown in the results of multiple linear regression analysis, namely Y = 0.000 + 0.179 + 0.114 + 0.622 + e. The t test (X1) counts 2.247 > ttable 1.984, meaning that the variable (X1) has a partial effect on (Y). For variables (X2) thitung 1.381 < ttabel 1.984 means that variables (X2) do not have a partial effect on (Y). For variables (X3) the calculation is 7.792 > ttable 1.984 means that the variable (X3) has a partial effect on (Y). Simultaneous statistical tests or F tests showed a calculated F of 70.226 > of fable 2.98 so that it can be concluded that the variables (X1), (X2) and (X3) have a simultaneous effect on (Y) can be accepted Based on the independent variable dominant test, the value of the influence of variables (X3) is 7.792 greater than that of variables (X1) and variables (X2). Based on the coefficient of determination, it shows a value of 0.687 from the results, it means that all free variables have a contribution of 68.7% to bound variables that have a very high influence, and the remaining 31.3% is influenced by other factors that are not included in the study.